The Principle of Legality in Criminal Proceedings - Corsei, Andreea (Acta Universitatis Danubius. Juridica, 2025)
The principle of legality is one of the fundamental pillars of criminal proceedings, with the role of guaranteeing respect for the fundamental rights and freedoms of persons involved in a judicial procedure. This principle requires that all acts and measures in the criminal process be based exclusively on the law, without deviations or discretionary interpretations (Dongoroz, Vintilă (coord.), 1976, p. 30). Enshrined in art. 1 para. (1) Criminal Procedure Code, the principle of legality ensures the conduct of the criminal process in accordance with legal norms, preventing abuses and providing the parties involved with a clear and predictable framework. This principle also derives from the provisions of the Romanian Constitution (2003), as well as from international standards, and is reaffirmed by the jurisprudence of the European Court of Human Rights (ECHR). Its applicability covers all stages of the criminal process – from criminal prosecution and trial, to the execution of final decisions. Legality concerns both substantive law norms (what is criminalized and sanctioned by law) and procedural law norms (the way in which the criminal trial is conducted).